Pharmacokinetics of Sugammadex Dosed by Actual and Ideal Body Weight in Patients With Morbid Obesity Undergoing Surgery - Kate Mostoller; Rebecca Wrishko; Lata Maganti; W. Joseph Herring; Mariëlle vanZutphen‐van Geffen (Wiley, 2021)
This analysis of a published study (NCT03346070) evaluated the pharmacokinetics (PKs) of sugammadex dosed by actual body weight (ABW) or ideal body weight (IBW) for reversal of moderate or deep neuromuscular block (M‐NMB or D‐NMB) in adults with morbid obesity. Adults with body mass index ≥ 40 kg/m2, ABW ≥ 100 kg, and American Society of Anesthesiologists (ASA) Class 3 were stratified by NMB agent (rocuronium or vecuronium) and randomized 1:1:1:1:1 to (i) M‐NMB, sugammadex 2 mg/kg ABW; (ii) M‐NMB, sugammadex 2 mg/kg IBW; (iii) M‐NMB, neostigmine 5 mg + glycopyrrolate 1 mg; (iv) D‐NMB, sugammadex 4 mg/kg ABW; and (v) D‐NMB, sugammadex 4 mg/kg IBW. Plasma samples for sugammadex quantification were collected predose, 2, 5, 15, 60, and 120 minutes, and 4, 6 hours postdose. Natural log PK parameters were analyzed using linear fixed effect model with treatment, mode (ABW and IBW), and mode by treatment interaction as fixed terms. The sugammadex PK profile showed rapid distribution followed by monophasic decline consistent with a two‐compartment model examined by dose and mode. Absolute sugammadex exposures were ~ 50% higher in the ABW vs. IBW group; dose‐independent parameters (clearance and volume of distribution) and terminal half‐life remained constant. Sugammadex PK parameter values increased in dose‐dependent, linear manner following dosing by ABW or IBW, such that PK continues to be predictive across the clinical dose range. In conjunction with previously published results showing faster recovery with ABW vs. IBW dosing across NMB agent and depth of NMB, these PK findings continue to support dosing by ABW in patients with morbid obesity irrespective of depth of NMB.